The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1080/10669817.2015.1110303
|View full text |Cite
|
Sign up to set email alerts
|

The application of mechanical diagnosis and therapy in lateral epicondylalgia

Abstract: Background: lateral epicondylalgia (LE) is a musculoskeletal diagnosis that causes pain and dysfunction in the lateral aspect of the elbow. Mechanical diagnosis and therapy (MDT) is an orthopaedic classification and treatment system based on mechanical and symptomatic response to repeated and sustained end-range movement. There has been no investigation of the association between MDT and patients diagnosed with LE. Case description: this report presents three patients matching the currently accepted diagnostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…Interestingly, 29/33 (87.9%) of these patients had a patho-anatomical diagnosis from a medical specialist. The presence of both an MDT and patho-anatomical diagnosis is most significant for those pathoanatomical conditions that have a degenerative or worsening prognosis, as the MDT classification Derangement is associated with positive short-and long-term prognosis [8]. Further, management of Derangement syndromes does not require medical or surgical intervention in comparison to the pathoanatomical diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, 29/33 (87.9%) of these patients had a patho-anatomical diagnosis from a medical specialist. The presence of both an MDT and patho-anatomical diagnosis is most significant for those pathoanatomical conditions that have a degenerative or worsening prognosis, as the MDT classification Derangement is associated with positive short-and long-term prognosis [8]. Further, management of Derangement syndromes does not require medical or surgical intervention in comparison to the pathoanatomical diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Bybee et al [21] found MDT-trained physical therapist students to be as reliable as experienced clinicians trained in MDT for diagnosis and treatment of patients with neck pain. Acceptable treatment and clinical outcomes have been achieved by MDT-trained student physical therapists under the guidance and monitoring of skilled MDT clinicians in the elbow, wrist, and cervical spine [8,17,22].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternate evaluative method, Mechanical Diagnosis and Therapy (MDT), assesses for mechanical changes of a joint as it relates to functional deficits. Doing so in the extremities has demonstrated rapid results in the shoulder, temporomandibular, knee, ankle, wrist, and elbow joints [3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The utility of patho-anatomical assessment in the lumbar spine and extremity has been shown to be unreliable [13,14] and poorly understood, as demonstrated in recent MDT literature [4,6,9,11,14,15]. Non-specific classification-based assessment and treatment systems, such as MDT, have demonstrated acceptable levels of reliability in the management of patients with spinal and extremity impairments [16,17].…”
Section: Introductionmentioning
confidence: 99%